Implementación de un modelo basado en factores críticos de éxito para que se contribuya a la gestión por resultados en Gobiernos Autónomos Descentralizados Parroquiales del cantón Chone - Saldarriaga Mendieta, Narcisa Jesús (2022)
Results-based management is based on the fact that public organizations set their standards of success and define their form of measurement, a situation that is often not implemented in the rural decentralized autonomous governments of Ecuador. adjust to the administrative reality of this type of institution, in order to have the necessary inputs duly contextualized and adjusted to the particularities of this type of institution, which allow for proper management to be carried out. The objective of this research was to implement a model based on critical success factors that contribute to the improvement of management by results in Decentralized Autonomous Parish Governments of the Chone canton, to achieve this, a systematic review of the literature was carried out that allowed structuring an initial list of 19 critical success factors. Then, based on the participation of 47 people through the application of the Delphi methodology, a list of 18 factors adjusted to the rural parish governments was structured, with these inputs a theoretical model was designed that establishes two phases, the implementation phase with 9 factors, and the operating phase with 9 factors, with a total of 18 critical success factors. Next, the theoretical model was applied in a case study considering the Decentralized Autonomous Parochial Government of Canuto; where it is shown that, of the 18 factors addressed, there are 16 factors that have a positive trend and two that have a negative trend, these two factors with a negative trend are related to the implementation of balanced scorecards susceptible to organizational computerization.